MSG368 - Sample Survey and Sampling Technique (Tinjauan Sampel dan Teknik Persampelan) - PPSM, Pusat Pengajian Sains Matematik (2022)
First Semester Examination 2021/2022 Academic Session February 2022 MSG368 - Sample Survey and Sampling Technique (Tinjauan Sampel dan Teknik Persampelan) Duration: 2 hours 45 minutes (Masa: 2 jam 45 minit)